“Você me faria um favor?” o futuro do pretérito e a expressão de polidez - Araujo, Andréia Silva (2014)
Politeness is a linguistic strategy used in order to avoid conflicts in verbal interaction. Politeness is an influential variable in sociolinguistic (cf. MEYERHOFF, 2006) to be related to language use: the pragmatic point of view, the social distance, power relations and the cost of enforcing variables are strongly involved in evaluation of linguistic strategies which are polished or not (BROWN; LEVINSON, 2011 [1987]); and sociolinguistic point of view, the sex/gender proves to be significant. Among the linguistic strategies used to express this value, we are interested in the verbal form of the future tense (FP). The use of this verb form may vary according to the value of temporal reference: past, present, future. A ware of this possibility of variation of the FP and considering that politeness can be seen on a continuum (the less polished the more polished), this research aimed to investigate the effects of pragmatic and sociolinguistic aspects of the uses FP as a function of time reference in the speech data of informants Itabaiana/SE. The general hypothesis guiding our research is that the FP alone does not encode politeness, but a set of contextual features in specific timeframes. To develop research in this perspective, we used as the sample speech corpus social network of university informants Itabaiana/SE. This sample consists of interactions conducted - the informants themselves lead to interaction - collected from a methodological model developed in our study specifically to capture the nuances of politeness, both in its pragmatic aspects as sociolinguistic. The collected data were categorized and analyzed statistically. The results were generated from three rounds statistics, with the variable rule the temporal reference of the form of FP (past, present, future) and the expression of politeness: past x present x future, past x no past, present x future. The results obtained in the first round showed that none of the controlled variables was significant in the expression of the phenomenon under study. In the second round, the program selected only two variables as significant: the verb form and the kind of discursive sequence. The results showed that the use of FP with past temporal reference is favored when the verb occurs with the assist going and the type of sequence is narrative. In the third round statistics, present x future, five variables were selected as significant: control of the interaction terms of sex/gender, verbal, linguistic parallelism, cost of enforcing and question-answer pair and comment. Among these, we highlight the results obtained with the control of the interaction terms of sex/gender which showed that men when they are in the field of the topic tend to use more verbal form of FP with present time reference. Regarding the variable cost of the levy, the results showed that the less imposing was the most recurring topic was the use of the FP with this timeframe. As for the question-answer pair variable and review, the results showed that the use of FP with present time reference was conditioned in contexts that were characterized as comment/contextualization the topic. In general, the use of theoretical and methodological collection procedures focusing on the pragmatic and sociolinguistic effects to capture the effects of politeness allowed us to demonstrate that there are significant differences regarding the use of the FP, especially regarding social distance and sex/gender.